The Promise and Perils of Health Internet of Things (HIoT). (Online Journal of Issues in Nursing, 2021)
The Internet of Things (IoT) refers to a physical world where smart devices or things and computers interconnect through wired or wireless networks to share and process information without human intervention. Health Internet of Things (HIoT) refers to a device that collects health related data from an individual. The explosive growth in HIoT to augment the delivery of healthcare is driving changes in clinical practice and patient-centered care, requiring new skills for providers. In this article I provide an overview of HIoT, factors fueling wearable market growth, and HIoT technology and usability challenges. Next, I present collaboration as a key to success in design and implementation of HIoT initiatives, identifying collaboration models useful to healthcare and consumer/patient teams. The discussion includes the technology adoption model (TAM) and associated adoption considerations. Finally, I identify implications for the nursing profession and provide HIoT recommendations for next steps that include engaging healthcare providers in the design and testing of HIoT products.